Envy in Christianity Compared to its Concept in Islam - Janan Hatem Nouri,; Khayal Saleh Hamad, (Islamic Sciences Journal, 2025)
ABSTRACT Envy is a reprehensible trait in all divine religions. It is the desire to remove blessings from others, a trait shared by all divine religions. Envy means the loss of a blessing from someone who deserves it, whether or not the blessing returns to the envious person. This leads to the disruption and destruction of society. The subject of envy revolves around wishing for the loss of blessings from others in all divine religions. Envy is forbidden in all circumstances, and in all divine religions, except for the envy of the immoral, who uses blessings to harm others and spread vice. Wishing for the loss of blessings is not forbidden. Treating envy is related to three aspects: the envious person: by repelling him from envy, urging him to congratulate himself if he sees something he likes, and calling him to spread peace; the envied person: by reciting verses from the Glorious Quran, seeking refuge in Allah from Satan and his helpers, and being patient; and the envious person and the envied person: by their sincerity towards Allah Almighty, their belief in fate and destiny, and fearing Allah Almighty.